The effect of sarpogrelate compared to aspirin in high- or very-high-risk diabetes for primary prevention - Soo Hyun Kang; Kilyoon Pack; Jung Ho Kim; Youngwoo Jang (Scientific Reports)
Abstract The benefit of aspirin in primary prevention for atherosclerotic cardiovascular diseases (ASCVD) is questionable due to bleeding complications. We analyzed the Korean National Health Insurance data to compare the efficacy and overall bleeding of sarpogrelate, an antiplatelet agent with lower bleeding risk, versus aspirin in high-/very-high-risk diabetic populations without prior ASCVD. The primary endpoint was net adverse clinical events (NACE), defined as a composite of efficacy and overall bleeding. The efficacy was a composite of all-cause death, myocardial infarction (MI) and stroke, whereas overall bleeding included intracranial hemorrhage (ICH) and gastrointestinal (GI) bleeding. A total of 10,778 high-/very-high-risk diabetic patients (9550 on aspirin, 1228 on sarpogrelate) were analyzed. After propensity score matching, sarpogrelate was linked to a lower incidence of NACE (HR:0.71; 95% CI 0.57–0.88), mainly driven by 62% reductions in overall bleeding (0.38; 0.17–0.81), a composite of 64% and 72% lower rate of GI bleeding and ICH, respectively. Additionally, there was no significant differences in MI or stroke between groups. In high- or very-high-risk diabetic patients without ASCVD, sarpogrelate use was associated with net clinical benefit mainly due to the reduction of significant reduction in overall bleeding events.